Analisis Strategi Dan Media Pembelajaran Sebagai Sebuah Sistem - Sunarti; M. Fadli; Syahputri , Intan (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2025)
Learning strategies and media are two essential and interrelated components within the learning system. A common problem that often arises is the mismatch between strategies and media with students’ characteristics and learning objectives. This study aims to analyze the role of learning strategies and media in supporting instruction as a unified system. The research method used is a literature study with a descriptive qualitative approach. Data were collected from various relevant literature sources and analyzed to describe the relationship between strategies, media, and other learning components. The results show that the appropriate and mutually supportive selection of learning strategies and media can enhance learning effectiveness, encourage active student participation, and strengthen the achievement of learning goals. Therefore, teachers need to consider strategies and media in an integrated manner in every stage of lesson planning.